Signifyin' the Unsayable Past in Toni Morrison's Beloved: The Case of the Newspaper Cutting - Kovács, Ágnes Zsófia (FOCUS: Papers in English Literary and Cultural Studies, 2023)
The essay surveys how Morrison’s Beloved rewrites African American history and the legacy of slavery by exposing racism encoded in language use through the example of the “newspaper cutting” in the novel. Beloved reverses existing accounts of the slave experience both from the perspective of the characters’ interactions and from the perspective of literary tropes used in it. The novel places oral and indirect communication over the formal system of writing, and by doing this produces a hybridized account of the slave experience. The paper focuses on how the contrast between written and oral storytelling is played out in the several uses of the newspaper cutting in the novel. The newspaper cutting tells Sethe’s story from the perspective of a white man, replete with images, while its several reproductions represent its chain of oral interpretations by the diverse racialized characters, eventually resulting in a hybridized story.